Concordance of Family and Staff Member Reports About End of Life in Assisted Living and Nursing Homes - Rich, Shayna E. (Oxford University Press, 2010)
Purpose: To identify differences in perspectives that may complicate the process of joint decision making at the end of life, this study determined the agreement of family and staff perspectives about end-of-life experiences in nursing homes and residential care/assisted living communities and whether family and staff roles, involvement in care, and interaction are associated with such agreement. Design and Methods: This cross-sectional study examined agreement in 336 family–staff pairs of postdeath telephone interviews conducted as part of the Collaborative Studies of Long-Term Care. Eligible deaths occurred in or within 3 days of leaving one of a stratified random sample of 113 long-term care facilities in four states and after the resident had lived in the facility ³15 days of the last month of life. McNemar p values and kappas were determined for each concordance variable, and mixed logistic models were run. Results: Chance-adjusted family–staff agreement was poor for expectation of death within weeks (66.9% agreement, κ = .33), course of illness (62.9%, 0.18), symptom burden (59.6%, 0.18), and familiarity with resident’s physician (59.2%, 0.05). Staff were more likely than family to expect death (70.2% vs 51.5%, p < .001) and less likely to report low symptom burden (39.6% vs 46.6%, p = .07). Staff involvement in care related to concordance and perspectives of adult children were more similar to those of staff than were other types of family members. Implications: Family and staff perspectives about end-of-life experiences may differ substantially; efforts can be made to improve family–staff communication and interaction for joint decision making.